PENGARUH PENGGUNAAN ICE BREAKING DALAM PELAJARAN IPAS TERHADAP MOTIVASI BELAJAR SISWA KELAS IV MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN - Dhea Mutia Jameliani; Dede Indra Setiabudi; Iis Humaeroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using ice breaking activities on students’ learning motivation in Natural and Social Sciences (IPAS) subjects for fourth-grade students at MI Ma’had Al-Zaytun. The research method used is a quantitative approach with a Pre-Experimental Design, employing a one-group pretest-posttest design. Data were collected through tests and questionnaires, with 44 fourth-grade students at MI Ma’had Al-Zaytun selected using purposive sampling techniques. Data analysis was carried out through normality tests, homogeneity tests, and Paired Sample T-Test using SPSS version 23. The results showed that the Paired Sample T-Test value was 0.000 (< 0.05), indicating that there is an effect of using ice breaking activities on students’ learning motivation. The average score increased from 65.16 in the pretest to 75.59 in the posttest, with a mean difference of 10.43 points. In addition, the questionnaire results showed that 66.71% of respondents gave positive and enthusiastic responses toward the use of ice breaking, indicating that this method is able to create a more enjoyable and interactive learning atmosphere. Based on these findings, it can be concluded that the use of ice breaking activities can be applied in IPAS learning for fourth-grade students at MI Ma’had Al-Zaytun, as it has a positive effect on students’ learning motivation. Keywords: Ice Breaking, Motivation, Natural and Social Sciences.